Hydranencephaly: A Cause of Increasing Head Size in A Nigerian Neonate - Daniyan, Olapeju Wunmi; Ezeanosike, Obumneme Benaiah; Onyebuchi, Amarachi Nnedinma; Okonkwo, Sunday Nnaemeka (Archives of Clinical and Medical Case Reports, 2020)
Hydranencephaly is a rare brain abnormality that is characterized by replacement of the cerebral hemispheres by cerebrospinal fluid. The incidence of hydranencephaly is estimated to be 0.5 per 1000 births. Various aetiologies have been proposed. These include bilateral occlusion of the internal carotid arteries and congenital infections like herpes simplex virus and Zika virus. Features of hydranencephaly include increasing head size, blindness , hypertelorism, seizures and excessive crying. Treatment is mainly supportive and children with hydranencephaly have a short life span. This is a case report of hydranencephaly in a 20 day old neonate. Baby looked normal at birth, developed increasing head size and excessive cry. Transfontanelle ultrasound scan revealed absence cerebral hemisphere with massive cerebrospinal fluid.